Sensitivity and rapidity of vegetational response to abrupt climate change - Peteet, Dorothy (The National Academy of Sciences, 2000)
Rapid climate change characterizes numerous terrestrial sediment records during and since the last glaciation. Vegetational response is best expressed in terrestrial records near ecotones, where sensitivity to climate change is greatest, and response times are as short as decades.